A green route to polyurethanes: oxidative carbonylation of industrially relevant aromatic diamines by CO2-based methyl formate. Issue 23 (28th August 2020) - Hussong, Christine; Langanke, Jens; Leitner, Walter
Abstract : Toluene-2, 4-diamine, 4, 4′-methylenedianiline and 2, 4-diaminomesitylene were converted directly into the corresponding dicarbamates via the CO2 -based intermediate methyl formate (MF) which can be regarded as a liquid source for CO/MeOH mixtures. Abstract : The oxidative carbonylation of toluene-2, 4-diamine (TDA) with methyl formate (MF), which can be produced from CO2, provides a possible route for the non-phosgene production of isocyanate precursors and enables a valuable utilization of the greenhouse gas. Extensive analysis of the product spectrum has provided detailed insight into the reaction network leading to the target product toluene-2, 4-dicarbamate (TDC) and the most important side products. The most prominent one has been identified as methylene-bridged tetracarbamate 5, which is also an interesting precursor for applications in polyurethane chemistry. The side products are caused by three different reaction paths: N -formylation by MF, condensation with in situ formed formaldehyde, and N -methylation by in situ formed dimethyl carbonate (DMC). The influence of the catalyst on product distribution was evaluated for PdCl2 /CuCl2 and a large number of heterogeneous Pd-catalysts. The oxidic support materials ZrO2, CeO2 and SiO2 were found to partially suppress the undesired side reactions leading to higher yields of TDC and tetracarbamate 5 . The ratio of TDC to 5 was demonstrated to be affected significantly by the choice of the support. The synthetic protocol was extended to the synthesis of dicarbamates from 4, 4′-methylenedianiline (MDA) and 2, 4-diaminomesitylene (17 ). These results encourage further investigations into the design of selective catalysts for the production of isocyanate precursors from CO2 as a C1 source.